Designing novel MgFe2O4 coupled V2O5 nanorod for synergetic photodegradation of tetracycline with enhanced visible-light energy harvesting: Photoluminescence, kinetics, intrinsic mechanism and bactericidal effect. (June 2022) - Janani, B.; Okla, Mohammad K.; Al-Amri, Saud S.; Mohebaldin, Asmaa; Alwasel, Yasmeen A.; AbdElgawad, Hamada; Abdel-Maksoud, Mostafa A.; Thomas, Ajith M.; Raju, Lija L.; Khan, S. Sudheer
Abstract: The present study focused on the enhancement of degradation of an important pharmaceutical pollutant, tetracycline with the help of nano photocatalyst under visible light irradiation. The study found that the synergetic effect of novel MgFe2 O4 –V2 O5 enhanced the photocatalytic degradation of tetracycline. Here, the photocatalyst was synthesized by sonochemical technique. Scanning electron microscopy image indicates the coupling of MgFe2 O4 nanocapsules on the surface of the V2 O5 nanorod. The bandgap of MgFe2 O4 (1.8 eV) and V2 O5 (2.5 eV) was shifted to 2.32 eV in MgFe2 O4 –V2 O5 to promote visible-light harvesting and it was depicted by the UV–visible DRS. XPS was used to identify the presence of chemical states with the existence of Mg 1s, Fe 2p, V 2p, and O 1s. The electrochemical impedance spectroscopy and photoluminescence spectra indicate the better separation of charge carriers owing to the formation of type II heterojunction formation. The tetracycline (25 mg/L) was degraded with MgFe2 O4 –V2 O5 (150 mg/L) that exhibited 3.3 and 5 folds enhanced rates than its counterparts (MgFe2 O4 and V2 O5 ) owing to synergism. The possible intermediate formation and degradation pathway was determined based on GC/MS analysis. TOC analysis of end products indicated maximum mineralization of tetracycline. The MgFe2 O4 –V2 O5 showed excellent recycling ability and reusability. The key photo-degradation of tetracycline was occurred by the generation of hydroxyl radicals. The MgFe2 O4 –V2 O5 exhibited high antibacterial activity that ensures the dual functionality of the prepared nanocomposites (NCs). Therefore, the present study displays MgFe2 O4 decorated V2 O5 nanorod as an ideal candidate for environmental remediation. Graphical abstract: Image 1 Highlights: MgFe2 O4 loaded on V2 O5 nanorod were fabricated. Sonochemical assisted co-precipitation technique was adopted for synthesis. The photocatalytic activity was enhanced by 3.3–5 times than individual NPs. The OH· play major role in tetracycline degradation. The particles exhibited excellent antibacterial activity.